Business analysis techniques 123 essential tools for success - Cadle, James; Paul, Debra; Hunsley, Jonathan; Reed, Adrian; Beckham, David; Turner, Paul (BCS Learning and Development, 2021)
The development of business analysis as a professional discipline has extended the role of the business analyst who now needs the widest possible array of tools and the skills and knowledge to be able to use each when and where it is required. This new edition provides 123 possible techniques and practical guidance on how and when to apply them